Hans Mincham interviewed by Hazel de Berg for the Hazel de Berg collection - Mincham, Hans, 1912-2007.; De Berg, Hazel, 1913-1984. (1964)
Mincham speaks about his various jobs; his teaching years; his book "The story of the Flinders Ranges".
Also available online
Transcript available (11 p.)
Keywords: Mincham, Hans, -- 1912-2007.; Mincham, Hans, -- 1912-2007. -- Interviews; Authors, Australian -- Interviews; Historians -- Australia -- Interviews